Consumer Color and Discoloration Thresholds for Purchase of Retail Ground Beef When Evaluating Packages of a Single Day of Display - K. R. Lybarger; E. S. Beyer; K. J. Farmer; L. A. Egger; L. N. Drey; J. L. Vipham; M. D. Zumbaugh; M. D. Chao; T. G. O'Quinn (Kansas Agricultural Experiment Station Research Reports, 2023)
Objective:This study utilized a simulated retail display to investigate the impact of ground beef color and discoloration on consumer purchase intent, while identifying the best objective measurements to predict consumer preferences of ground beef on the same day of retail display. Study Description:For this study, 180 1-lb 80% lean/20% fat ground beef loaves were assigned to a specific day of retail display (day 0–9). Consumers (n= 318) and trained descriptive panelists assessed ground beef samples, with a single day of display evaluated per consumer group. Spectral data andL*(lightness),a* (redness), andb* (yellowness) values were collected. Simple linear and logistic regressions were calculated for consumer ratings. Lastly, Pearson correlation coefficients were calculated for sensory and objective measurements. The Bottom Line:Consumer intent to purchase ground beef at varying days of retail display can be predicted by the objective measures used in this study. Moving forward, these models can provide ground beef producers and retailers with an indication of potential consumer purchasing behaviors for ground beef at varying levels of discoloration to prevent waste and maximize profits.
Keywords: consumer; color; ground beef